SOSIALISASI DAN PENDAMPINGAN APLIKASI WEBSITE SISTEM INFORMASI DESA (SID) DI DESA BEDAH LAWAK, KABUPATEN JOMBANG - Zulfikar Zulfikar; Primaadi Airlangga; Fachrul Fatah Al Rasyid; Indrajid Permana; Luthfi Firdaus (Fakultas Teknik, Universitas Bangka Belitung, 2023)
The problem that is often faced by village government officials in terms of efficiency and improving performance is the lack of skills in managing records so that public services are not optimal. Efforts are being made to build an information system in the form of website communication media and a village information system so that it can assist and improve the performance of village officials. Implementation of community service in the form of SID website design activities developed in Bedah Lawak Village, Tembelang District, Jombang Regency using a simple interface design. Furthermore, socialization, mentoring, and evaluation of activities are carried out to see the sustainability of the community service program. This service activity succeeded in designing the SID website and socialization was carried out in general the village community was very enthusiastic and very helpful in the performance of village officials. This website is able to provide information for the village community and support the performance of village officials for easy access to public services. The results of the SID Web seminar showed that 37% of the people were satisfied and 50% were very satisfied with the existence of the village website and were able to improve the performance of village officials by 67%. This shows that the SID website is very helpful for the community in accessing information and providing easy service to administrative needs in the village. In addition, the SID website is able to improve the performance of the village apparatus in serving the needs of the community.